Critical Thinking In Elt: How Cooperative Learning Affects The Efl Learners’ Critical Thinking Aspects - Jaya Nur Iman; Nike Angraini (Universitas Indo Global Mandiri, 2019)
AbstractThis research attempted to see whether the cooperative leaning was impactful on EFL learners’ critical thinking aspects. Non-equivalent pretest and posttest control group design of comparison group design was used in this research. The population of the research was all of the undergraduate students of University of Indo Global Mandiri. Forty students were selected as the sample purposively in the experimental group (treatment group) and control group (non-treatment group), respectively. A critical thinking rubric was employed to measure the EFL learners’ critical thinking(aspects) and critical thinking aspects(total). The research findings revealed that (1) there was a significant improvement on the EFL learners’ critical thinking(aspects) and critical thinking (total), (2) There was a significant mean difference on the EFL learners’ critical thinking(aspects) and critical thinking aspects(total), (3) there was a significant contribution of the critical thinking skill (aspects) and critical thinking aspects(total) in which the aspects of framing personal responses and acknowledging other perspectives had the lowest contribution and the aspects of recoqnizing stakeholders and context had the highest contribution. In conclusion statistically the cooperative learning was significantly impactful on the EFL learners’ critical thinking aspects in English language teaching.Keywords: Cooperative learning, critical thinking aspectsAbstrak Penelitian ini berusaha untuk melihat apakah pembelajaran kooperatif berdampak pada aspek berpikir kritis peserta didik EFL. Penelitian ini menggunakan desain penelitian non-equivalent pretest and posttest control group design of comparison group design. Populasi dari penelitian ini adalah semua mahasiswa sarjana dari Universitas Indo Global Mandiri. Empat puluh siswa dipilih sebagai sampel secara purposif dalam kelompok eksperimen (kelompok perlakuan) dan kelompok kontrol (kelompok non-perlakuan). Rubrik berpikir kritis digunakan untuk mengukur pemikiran kritis (aspek) pembelajar EFL dan aspek berpikir kritis (total). Temuan penelitian mengungkapkan bahwa (1) ada peningkatan yang signifikan pada pemikiran kritis (aspek) peserta didik EFL dan pemikiran kritis (total), (2) Ada perbedaan rata-rata yang signifikan pada pemikiran kritis peserta didik EFL (aspek) dan aspek berpikir kritis (total), (3) ada kontribusi signifikan dari keterampilan berpikir kritis (aspek) dan aspek berpikir kritis (total) di mana aspek membingkai tanggapan pribadi dan mengakui perspektif lain memiliki kontribusi terendah dan aspek dari para pemangku kepentingan dan konteks yang memiliki kontribusi tertinggi. Kesimpulannya secara statistik pembelajaran kooperatif berdampak signifikan pada aspek berpikir kritis peserta didik EFL dalam pengajaran bahasa Inggris.Kata kunci: pembelajaran kooperatif, aspek berpikir kritis